Effects of Litterfall on the Accumulation of Extracted Soil Humic Substances in Subalpine Forests - Wei, Xinyu; Yang, Yulian; Shen, Ya; Chen, Zihao; Dong, Yuliang; Wu, Fuzhong; Zhang, Li (Frontiers in Plant Science, 2020)
Plant litter is one of the main sources of soil humus, but which can also promote primary humus degradation by increasing microbial activity due to the higher availability of energy released, resulting in a confusing relationship between litterfall and soil humus. Therefore, an in situ incubation experiment was carried out in three subalpine forests (coniferous, mixed and broadleaved forests) on the eastern Qinghai-Tibetan Plateau. We set up two treatments, the one allowed litterfall to enter the soil normally and the other prevented litterfall to enter the soil. Soils were sampled in October, January, March, and May from May 2017 to May 2018. By assessed the litterfall production, the content of total extracted humus, humic acid and fulvic acid in the topsoil (0-20 cm) in each incubation period, we determined the impact of litterfall on the content of humus extracted from the soil during the freezing and the growing season. Over one-year incubation, soil total extracted humus and humic acid showed considerable decreases in the treatment of retained litterfall in the mixed forest rather than in the coniferous and broadleaved forests. Moreover, litterfall significantly reduced the contents of soil total extracted humus and humic acid during the growing season in all three forests, while only reduced soil humic acid content in the broadleaved forest in the freezing season. However, the relationship between litterfall and soil extracted humic substances was greatly regulated by the seasonal dynamics of litter types and litter production. The larger the amount of litterfall was, the more litterfall could promote the reduction of soil extracted humic substances. Compared with a single type of broadleaf or needle litter, mixed litterfall could promote a higher degradation of soil humic substances. However, broadleaf litter might lead to much greater decreases in soil humic substance than needle litter because of more decomposable. These results indicate that a longer growing season and a shorter winter caused by ongoing global warming may alter the relationships between litterfall and extracted humic substances, further disrupting the carbon balance of forest ecosystems in the subalpine forests.f forest ecosystems in the subalpine forests.